Intestinal parasitic infections in children living in selected barangays with urban slums along Iloilo river - Aguro, Eric.; Banaag, Arlene; Jacobe, Venus N. (2006.)
This cross-sectional study was performed to determine the intestinal parasitic infection in children age 0-13 years old in three selected barangays with urban slums located alongside Iloilo River. A total of 127 stool samples from 65 males and 62 females were examined by utilizing formalin-ether concentration technic (FECT) and direct wet mount therafter using Lugol's solution. It was found out that 59.8 percent of the children examined were positive for one or more intestinal parasites.
Special Problem (Undergraduate, Bachelor of Science in Public Health)College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Intestinal parasitic infection